Synthesis of Au-Pd-NPs Materials and Application as Electrochemical Sensor of Hydroquinone in Cosmetics - Riyanto; Mardliyaliari, Safira; Sabrina, Alya; Ridho, Muhammad (Science and Technology Indonesia, 2025)
Hydroquinone is a hazardous and toxic chemical often added to cosmetics due to bleaching properties. It is commonly analyzed in cosmetics using expensive and time-consuming instruments, showing the need for a cheap, fast, and sensitive hydroquinone electrochemical sensor. The performance of electrochemical sensor to detect hydroquinone is determined by the working electrode. Therefore, this study aimed to explore the synthesis of Au-Pd-NPs working electrode and application as electrochemical sensor of hydroquinone in cosmetics. Synthesis process was carried out by preparing Au-NPs using banana peel extract (Musa acuminata Colla) as a bioreductor, followed by adding H2PdCl4 solution. Au-NPs nanoparticle was confirmed using Ultraviolet-Visible spectrophotometer, which showed maximum wavelength of 550 nm. The indication of Au-Pd-NPs was shown by the peak at the same wavelength. The FTIR spectrum showed pectin which acted as a bioreductant agent in synthesis of nanoparticles. The results of the TEM image showed that Au-NPs had a spherical shape in the dark field with a diameter of 38.5 ± 3.3 nm and a Pd shell layer around the Au core in the bright field with a diameter of 12.4 ± 2.6 nm. The solid Au-Pd-NPs materials were made into a composite electrode by adding PVC and tetrahydrofuran as solvents. Electrochemical response of Au-Pd-NPs electrode was tested by cyclic voltammetry in ferricyanide and PBS solutions at pH 7.0. Based on CV in the ferricyanide system, it shows that Au-Pd-NPs electrode produces peak oxidation and reduction currents ten times higher than Au-NPs. These data indicate that Au-Pd-NPs are more reactive and sensitive than Au-NPs electrodes. The Au-Pd-NPs electrode was used to analysis the concentration of hydroquinone in cosmetics samples. Electrochemical response showed a linearity (R2) of 0.9935 in concentration range of 0-60 mM, containing 1.12% hydroquinone.